Поняття права внутрішнього судноплавства та пов’язані з ним питання (за матеріалами Німеччини і України) - Мошак, Г. Г. (НДІ ПЗІР НАПрН України, 2022)
У статті розглянуто поняття права внутрішнього судноплавства та пов’язані з ним питання за матеріалами Німеччини та України. Актуальність дослідження поняття права внутрішнього судноплавства обумовлюється його важливістю для науки і практики та недослідженістю в Україні. Метою дослідження є сприяння вдосконаленню поняття права внутрішнього судноплавства. Використовувалися методи аналізу та порівняння теоретичних понять і правових норм, а також метод соціально-економічної статистики для аргументації пропозицій по досліджуваній темі. Показано зв’язок між поняттями права внутрішнього судноплавства та внутрішнього водного шляху. Використано німецькомовні твори В. Коріота, Я.-Х. Крумме, Т. Вальдштейна, Г. Голланда. Визначено предмет та спрямованість досліджень українських науковців П.Є. Казанського, А.В. Кулько, А.П. Єфименко, Є.А. Самойленко та Г.В. Самойленко. Результати дослідження дозволили сформулювати поняття права внутрішнього судноплавства як сукупність переважно приватноправових норм, котрі регулюють відносини у сфері судноплавного використання внутрішніх водних шляхів. Здійснено аналіз теоретичних і нормативних основ поняття внутрішнього водного шляху та показників рівня соціально-економічного розвитку України і Німеччини, що впливають на стан та розвиток понять і норм права внутрішнього судноплавства. Показано обсяг можливого збільшення перевезень вантажів, котрі у змозі стимулююче вплинути на розвиток основних питань права внутрішнього судноплавства. Пропонується запозичити передовий німецький досвід та тимчасове розв’язання проблеми дефіциту нормативних актів у сфері внутрішнього водного транспорту України. Problem setting. The article deals with the concept of inland navigation law and related issues based on the materials of Germany and Ukraine. The relevance of the study of the concept of inland navigation law is due to its importance for science and practice and its lack of research in Ukraine. The methods of analysis and comparison of theoretical concepts and legal norms, as well as the method of socio-economic statistics were used to argue proposals on the topic under study. Analysis of recent researches and publications. The connection between the concepts of inland navigation law and inland waterway is shown. The German-language works of W. Coriot, J.-H. Krumme, T. Wal-dstein, G. Holland. The subject and direction of the research of Ukrainian scientists P.E. Kazansky, A.V. Kulko, A.P. Efymenko, E.A. Samoilenko and G.V. Samoilenko were determined. Target of the research is to contribute to the improvement of the concept of inland navigation law. Article’s main body. The research was carried out in several stages: from a large number of sources, only those classified as essential by the Institute of Transport and Traffic Law of the University of Mannheim (Germany), one of the most authoritative specialized institutions in Europe, were selected and analyzed; then the commenting on the German law on private law relations of inland shipping and other sources, translated by us into Ukrainian, was completed; in conclusion, the results obtained in Ukraine are compared with the data of German authors. The study showed that the concept of «inland navigation law» is closely related to the definition of the terms inland navigation and inland waterway. The current legislation of Ukraine and the law do not provide an unambiguous formulation of the concept of inland shipping. The assumption that shipping is called inland because it uses inland waterways only partially captures the point. Inland waterways are actually used mainly by inland water transport, the activity of which is regulated by the law of inland navigation. Sea routes mostly serve maritime navigation, which is regulated by maritime law. However, the division of shipping into sea and inland based on the specified criterion (characteristics of the routes used) does not agree with the norms of domestic law and the conclusions of foreign studies. Conclusions and prospects for the development. The results of the study allowed to formulate the concept of inland navigation law as a set of mainly private law norms that regulate relations in the field of navigable use of inland waterways. The analysis of the theoretical and normative bases of the concept of inland waterway and indicators of the level of socioeconomic development of Ukraine and Germany, which affect the state and development of the concepts and norms of inland navigation law, is carried out. The volume of possible increase of cargo transportation, which can stimulate the development of the main issues of inland navigation law, is shown. It is proposed to apply the advanced German experience and temporary solution of the problem of deficiency of normative acts in the field of inland water transport of Ukraine.
Keywords: судноплавство; внутрішній водний шлях; правове регулювання; navigation; inland waterway; law regulation